Indeks Vol. 13, Nomor 1–2, Tahun 2015 - Dewan Redaksi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Indeks Vol. 13, Nomor 1–2, Tahun 2015